1999
DOI: 10.1046/j.1365-2672.1999.00676.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of an L‐glutamate‐induced acid tolerance response which involves the functioning of extracellular induction components

Abstract: R .J . R O WB UR Y , T .J . HU MP H RE Y A N D M . G O OD SO N 1999. Escherichia coli became more acid tolerant following incubation for 60 min in a medium containing L-glutamate at pH 7·0, 7·5 or 8·5. Several agents, including cAMP, NaCl, sucrose, SDS and DOC, prevented tolerance appearing if present with L-glutamate. Lesions in cysB, hns, fur, himA and relA, which frequently affect pH responses, failed to prevent L-glutamate-induced acid tolerance but a lesion in L-glutamate decarboxylase abolished the respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
(33 reference statements)
1
12
0
Order By: Relevance
“…AstE hydrolyzes N 2 -succinylglutamate into succinate and L-glutamate. L-glutamate has been identified to be involved in acid stress response in E. coli [53], [54]. Recent studies have demonstrated that n-butanol response in Lactobacillus brevis [55] downregulated the acid stress response significantly (Winkler and Kao, manuscript submitted).…”
Section: Resultsmentioning
confidence: 99%
“…AstE hydrolyzes N 2 -succinylglutamate into succinate and L-glutamate. L-glutamate has been identified to be involved in acid stress response in E. coli [53], [54]. Recent studies have demonstrated that n-butanol response in Lactobacillus brevis [55] downregulated the acid stress response significantly (Winkler and Kao, manuscript submitted).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that phosphate and cAMP help in acid adaptation (Rowbury et al . ). It is possible that the reduced concentrations of the hydroxylamine in the pH 3·6 cells could be the result of its conversion to ammonium by hydroxylamine reductase (Bernheim and Hochstein ).…”
Section: Discussionmentioning
confidence: 97%
“…These results indicate that rpoS deficiency in HEC-RM did not affect acid resistance when they were adapted under moderate acid condition. Although rpoS is a regulatory gene involved in acid resistance, E. coli has two other non-rpoSdependent acid resistance mechanisms enhanced by either glutamate or arginine, which are associated with the consumption of protons by decarboxylase systems when these amino acids are present in the growth medium (13,24,33). TSB contains both amino acids; therefore, the activities of these two nonrpoS-dependent systems probably account for the observation that the rpoS-deficient mutant still possessed acid resistance in simulated gastric fluid by prior exposure to moderate acid condition.…”
Section: Resultsmentioning
confidence: 99%